Getting in Gear for Global Competition: Pacts on Employment and Competitiveness in the EU Automobile Industry - Zagelmeyer, Stefan (Transfer, 2001)
During the 1990s, company or plant-level collective agreements on employment and competitiveness were forged at most car producers in the European Union. These pacts aim at maintaining or creating jobs and at improving the competitiveness of the plant or company in intra-conglomerate as well as inter-company competition. This paper analyses these employment pacts and discusses their implications for labour relations. It concludes that these pacts should not just be seen as examples of concession bargaining, but rather as emerging forms of cooperative labour relations, focusing on adjusting the governance of the employment relationship to the imperatives of joint competitive succes